2020
DOI: 10.1038/s41388-020-01567-7
|View full text |Cite
|
Sign up to set email alerts
|

RAS-protein activation but not mutation status is an outcome predictor and unifying therapeutic target for high-risk acute lymphoblastic leukemia

Abstract: Leukemias are routinely sub-typed for risk/outcome prediction and therapy choice using acquired mutations and chromosomal rearrangements. Down syndrome acute lymphoblastic leukemia (DS‐ALL) is characterized by high frequency of CRLF2‐rearrangements, JAK2‐mutations, or RAS‐pathway mutations. Intriguingly, JAK2 and RAS-mutations are mutually exclusive in leukemic sub‐clones, causing dichotomy in therapeutic target choices. We prove in a cell model that elevated CRLF2 in combination with constitutionally active J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Indeed, targeting of JAKs, for example, by proteolysis-targeting chimeras (PROTACs) directed against JAKs, has been shown to be a potent treatment for CRLF2 -rearranged ALL 122 . In Down syndrome-associated ALL, in which there is a high rate of rearrangement of CRLF2 , TSLP increases binding of the tyrosine phosphatase PTPN11 to RAS, resulting in RAS protein activation, which promotes ALL cell growth 123 .…”
Section: Tslp and Cancermentioning
confidence: 99%
“…Indeed, targeting of JAKs, for example, by proteolysis-targeting chimeras (PROTACs) directed against JAKs, has been shown to be a potent treatment for CRLF2 -rearranged ALL 122 . In Down syndrome-associated ALL, in which there is a high rate of rearrangement of CRLF2 , TSLP increases binding of the tyrosine phosphatase PTPN11 to RAS, resulting in RAS protein activation, which promotes ALL cell growth 123 .…”
Section: Tslp and Cancermentioning
confidence: 99%
“…It is currently unknown whether CRLF2 r/ JAK2 r-mutant ALL preclinical models are susceptible to JAK inhibitor resistance through this same mechanism. However, activation of alternative signaling pathways such as C-MYC and MAPK/ERK have been identified in CRLF2 r/ JAK2 r-mutant ALL 47 , 48 , suggesting that in this setting, JAK inhibitor resistance may develop via upregulation of alternative signaling pathways potentially in preference to acquired mutations within the JAK2 ATP-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a new study revealed that the activation of KRAS wild-type alone is sufficient to induce oncogenic KRAS properties in cases of Down Syndrome (DS)-ALL [17]. Approximately 60% of DS-ALL cases harbor cytokine receptor-like factor 2 (CRLF2) rearrangements, 32% of cases harbor JAK2 mutations and 36% harbor mutations in the RAS-MAPK pathway.…”
Section: Blood Cancersmentioning
confidence: 99%
“…Both JAK2 and RAS pathway mutations are mutually exclusive. However, high CRLF2 levels and increased activation of JAK2 sufficiently activate wildtype KRAS in 80% of DL-ALL cases, suggesting that therapeutics inhibiting overstimulated KRAS are needed [17].…”
Section: Blood Cancersmentioning
confidence: 99%